Career Guidance Based on Krumboltz's Social Learning Theory to Develop Students' Career Decisions - Ginting, Putri Angelina br; Taufiq, Agus; Supriatna, Mamat (Department of Guidance and Counseling, FIP, Undiksha, 2024)
Career decisions impact an individual's success and satisfaction in their career. Various factors can hinder teenagers' career decision-making, affecting their future career paths. This research aims to produce career guidance based on Krumboltz's social learning theory that is effective for developing students' career decisions. This research is quantitative research using a positivism paradigm with a quasi-experimental design experimental method. Participants in this research involved 493 people, namely class XI high school students, guidance and counseling expert lecturers, and high school guidance and counseling teachers. Sample selection was carried out using a purposive sampling technique taken based on the class with the lowest score through data collection using an instrument in the form of a career decision questionnaire that had been developed and tested rationally. The data analysis technique used is inferential statistics with the non-parametric statistical testing technique Mann Whitney u test. The research results show a sign value (2-tailed) of 0.008<0.05, which means that career guidance based on Krumboltz's social learning theory is effective for developing students' career decisions. It can be concluded that career guidance based on Krumboltz's social learning theory to develop students' career decisions can be used in career guidance in high school. The principles of Krumboltz's theory in a context that has never been explored before, provide a new perspective that shows novelty in the career guidance approach. This research implies that Guidance and Counseling teachers can apply Krumboltz's social learning theory in career guidance to assist students in making career decisions.